2008
DOI: 10.1080/07391102.2008.10507231
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Natural RNA Sequences from RNA Shape, Thermodynamic Stability, Mutational Robustness, and Linguistic Complexity by Evolutionary Computation

Abstract: The process of designing novel RNA sequences by inverse RNA folding, available in tools such as RNAinverse and InfoRNA, can be thought of as a reconstruction of RNAs from secondary structure. In this reconstruction problem, no physical measures are considered as additional constraints that are independent of structure, aside of the goal to reach the same secondary structure as the input using energy minimization methods. An extension of the reconstruction problem can be formulated since in many cases of natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The comparison depicted in Figure 4 was performed for an miR-146 example test case taken from [15], after it was verified in [9] by taking a collection of miRNAs from the microRNA registry [16] that miRNA precursors are significantly more thermodynamically stable and mutationally robust than random RNAs. Therefore, even though from an initial inspection of the structure drawings in Figure 4 it may appear that the RNAinverse result is in better agreement to the wild-type than the RNAexinv result, it should be noted that the values of the thermodynamic stability and mutational robustness of miR-146 are not taken into account when designing sequences with RNAinverse.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison depicted in Figure 4 was performed for an miR-146 example test case taken from [15], after it was verified in [9] by taking a collection of miRNAs from the microRNA registry [16] that miRNA precursors are significantly more thermodynamically stable and mutationally robust than random RNAs. Therefore, even though from an initial inspection of the structure drawings in Figure 4 it may appear that the RNAinverse result is in better agreement to the wild-type than the RNAexinv result, it should be noted that the values of the thermodynamic stability and mutational robustness of miR-146 are not taken into account when designing sequences with RNAinverse.…”
Section: Resultsmentioning
confidence: 99%
“…To incorporate the physical measures listed above as constraints in the inverse RNA folding problem, the problem must first be relaxed from secondary structure to shape, as our previous simulations showed that such constraints can yield no solution [9]. Thus, instead of the RNA secondary structure, we used the simplified coarse-grained representation [13,14] as its shape.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, in many viruses it is RNA that contains genetic information of virus such as HIV and therefore regulates the functions of such virus. RNA has recently become the center of much attention because of its catalytic properties, leading to an increased interest in obtaining structural information (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Although more and more RNA secondary structures have been accumulated, we know little about their functions.…”
Section: Introductionmentioning
confidence: 99%